Measuring the ability of heritage tree in mitigating urban heat island (UHI) through GIS and remote sensing integration in Taiping, Perak / Nor Suhaida Yusof - Yusof, Nor Suhaida (2020)
Every tree species provides different cooling effects depending on their tree characteristics. Evergreen species such as heritage tree are significant in reducing the surface temperature. In particular, heritage trees do have environmental implications which provide a lot of benefits for the environment and human health. However, the cooling effects from tree species are differ by areas they are planted. The different albedo value land cover features materials have influenced the performance of tree species in giving the cooling effects to the environment. Therefore, the aim of the study is to determine the ability of heritage trees surface temperature with land cover features in mitigating urban heat island (UHI) in Taiping Old Town. The research investigated the internal and external factors of heritage trees in reducing the Land Surface Temperature (LST) in study area. The data was utilized from satellite imagery of Landsat 8 OLI that were obtained from USGS website. These data were processed using ERDAS IMAGINE 2014 software using graphical model function technique to generate the LST distribution of study area. Field observation was also conducted to measure the heritage trees characteristics based on the vegetation parameter of cooling effect. Then, the data was processed using the GIS tools for further data analysis. These results later correlated to measure the relationship between heritage trees and LST distribution at study area. The result indicates that the contribution of heritage trees is dominant in the vegetation parameter of cooling effect in which it could only contribute 24.8% of cooling effect to the surrounding area. This is because the cooling effects from heritage trees were influenced by external related factors. The albedo values of land cover features for both man-made and natural features showed the shocking result by showing linear positive relationship with the R2 values equals to 0.708. This result was contradicted from previous research that showed higher albedo values resulted to lower surface temperature. However, the findings of the research revealed that the lower albedo values resulted to lower surface temperature. This is because the higher frequency of heritage trees planted at the hard surface caused higher ability to reduce the LST in urban areas. In conclusion, the finding of this research could significantly contribute to the landscape practice and design, toward mitigate UHI effects.